Study on Dynamical System with Time-delay - Mondal, Amit; Islam, Nurul (Journal of Applied Nonlinear Dynamics, 2026)
In this paper, stability analysis of the nonlinear time-delayed Sprott system is made by applying a small perturbation near the critical point. Next, we will discuss a scheme for delay synchronization. To achieve our claim, we will make the chaos synchronization between the coupled Sprott system with delay parameters. Here, we will discuss five distinct cases. Numerical simulation is done to verify our claim.